Experimental and Theoretical Study on Influence of Different Charging Structures on Blasting Vibration Energy - Wenbin Gu; Zhenxiong Wang; Jianghai Chen; Jianqing Liu; Ming Lu (Shock and Vibration)
As an important parameter in blasting design, charging structure directly influences blasting effect. Due to complex conditions of this blasting and excavating engineering in Jiangsu, China, the authors carried out comparative researches with coupling structure, air-decoupling structure, and water-decoupling structure. After collecting, comparing, and analyzing produced signals on blasting vibration, the authors summarized that when proportional distances are the same, water-decoupling structure can reduce instantaneous energy of blasting vibration more effectively with more average rock fragmentation and less harm of dust. From the perspective of impedance matching, the present paper analyzed influence of charging structure on blasting vibration energy, demonstrating that impedance matching relationship between explosive and rock changes because of different charging structures. Through deducing relationship equation that meets the impedance matching of explosive and rock under different charging structures, the research concludes that when blasting rocks with high impedance, explosive with high impedance can better transmits blasting energy. Besides, when employing decoupling charging, there exists a reasonable decoupling coefficient helping realize impedance matching of explosive and rock.